Equipment for germ-free caesarean section and baby care - Trávnícek, J; Mandel, L; Kasal, P; Král, J; Mydlil, V (Folia microbiologica, 1977)
A germ-free isolator system was designed and constructed. It permits a sterile caesarean section and rearing of an infant under germ-free conditions. The system includes a plastic surgical and rearing isolator and two supply isolators; one of the supply isolators served as a transport mobile unit of staff participating in the sterile caesarean section and in the postnatal care of the germ-free newborn underwent to a special training and all of them were able to meet the high requirements of this work. The surgery itself was without complications. The newborn was absolutely sterile up to the age of 1 month; afterwards the infant was gradually colonized with selected strains of bacteria and thus prepared for conventialization. In the course of this work further possibilities of application of gnotobiological techniques in pediatrics were proposed (e.g. care of premature, high-risk neonates).
Keywords: péče o kojence; Cesarean Section; inkubátory kojenecké; Immunologic Deficiency Syndromes; gnotobiologické modely; syndromy imunologické nedostatečnosti; císařský řez; Infant, Newborn; Swine; novorozenec; Sterilization; zvířata; Humans; Incubators, Infant; Germ-Free Life; Infant Care; prasata; sterilizace; lidé; Animals